2015
DOI: 10.1105/tpc.15.00335
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Variation in Responses to Root Spatial Constraint within Arabidopsis thaliana

Abstract: ORCID IDs: 0000-0001-9298-629X (B.J.); 0000-0001-5759-3175 (D.J.K.)Among the myriad of environmental stimuli that plants utilize to regulate growth and development to optimize fitness are signals obtained from various sources in the rhizosphere that give an indication of the nutrient status and volume of media available. These signals include chemical signals from other plants, nutrient signals, and thigmotropic interactions that reveal the presence of obstacles to growth. Little is known about the genetics un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…quantified the levels of 2000 analytes representing the specialized metabolism of Arabidopsis in a population derived from the L er and Cvi ecotypes (Keurentjes et al ., ). Much of the follow‐up work on Arabidopsis has been carried out by the laboratories of Dan Kliebenstein and Lothar Willmitzer (Lisec et al ., ; Rowe et al ., ; Joseph et al ., ,b). Their work addressed many aspects of the genetics of metabolism, including a comparative analysis of population types, and the evaluation of heterosis, heritability and the environmental plasticity of the plant metabolome (Joseph et al ., ).…”
Section: Gene Functional Annotation and Metabolic Quantitative Trait mentioning
confidence: 99%
See 1 more Smart Citation
“…quantified the levels of 2000 analytes representing the specialized metabolism of Arabidopsis in a population derived from the L er and Cvi ecotypes (Keurentjes et al ., ). Much of the follow‐up work on Arabidopsis has been carried out by the laboratories of Dan Kliebenstein and Lothar Willmitzer (Lisec et al ., ; Rowe et al ., ; Joseph et al ., ,b). Their work addressed many aspects of the genetics of metabolism, including a comparative analysis of population types, and the evaluation of heterosis, heritability and the environmental plasticity of the plant metabolome (Joseph et al ., ).…”
Section: Gene Functional Annotation and Metabolic Quantitative Trait mentioning
confidence: 99%
“…Much of the follow‐up work on Arabidopsis has been carried out by the laboratories of Dan Kliebenstein and Lothar Willmitzer (Lisec et al ., ; Rowe et al ., ; Joseph et al ., ,b). Their work addressed many aspects of the genetics of metabolism, including a comparative analysis of population types, and the evaluation of heterosis, heritability and the environmental plasticity of the plant metabolome (Joseph et al ., ). Work in the Kliebenstein laboratory additionally quantified the influence of genetic information from the organellar genomes on the metabolome (Joseph et al ., ,b), studied epistatic interactions and defined novel potential biochemical networks (Rowe et al ., ).…”
Section: Gene Functional Annotation and Metabolic Quantitative Trait mentioning
confidence: 99%
“…To obtain a complementary picture of the molecular bases underlying plant-plant interactions identified up to date, we examined studies where focal plants have been directly challenged by neighbor plants. Therefore, we have not considered studies performed in artificial environments designed to simulate plant-plant interactions, such as shade (Nagatani et al, 1993;Reed et al, 1993Reed et al, , 1994 or root spatial constraint (Joseph et al, 2015). Although simulated environments are highly powerful to decipher the molecular mechanisms underlying the perception of a particular signal (Gundel et al, 2014; Ballar e and Pierik, 2017), it does not embrace the range and complexity of signals that are perceived by a focal plant directly interacting with a neighbor plant (Moriles et al, 2012;Horvath et al, 2015; Figure 1).…”
Section: The Genetics Of Natural Variation Of Plant-plant Interactionsmentioning
confidence: 99%
“…For example, among the 56 genes functionally validated for being associated with natural variation in response to biotic interactions in the model plant Arabidopsis thaliana, more than one-third confer resistance to herbivory while the rest of the genes are more-or-less evenly distributed among interactions with viruses, bacteria, fungi and oomycetes (Roux and Bergelson, 2016). The only gene identified as involved in plant-plant interactions underlies responses to root spatial constraints (used as proxy for thigmotropic responses to other plants within the rhizosphere) and not the direct response to a neighbor plant (Joseph et al, 2015). In addition, in early 2017, 35 Genome-Wide Association studies (GWAS) reported the fine mapping of genomic regions associated with natural variation of plant response (either crops or natural species) to pathogen infection (Bartoli and Roux, 2017), whereas only one GWAS reported the identification of QTLs underlying plant-plant interactions (Baron et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, epistasis and GxE may themselves interact. Significant three-way interactions (GxGxE) have been documented in both field and laboratory studies (Caicedo et al 2004; Zhu et al 2014; Joseph et al 2015; Monnahan and Kelly 2015b).…”
Section: Discussionmentioning
confidence: 99%